ANALYSIS OF ADVERSE DRUG REACTIONS TO ANTIRETROVIRALS USE IN A SECONDARY HOSPITAL - Vitarani Dwi Ananda Ningrum; Nadia Hanrisari; Tiara Amalia; Sufiyah (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Although antiretrovirals (ARV) evidently extend the life expectancy of people living with HIV/AIDS (PLWH), their associated Adverse Drug Reactions (ADRs) are unavoidable, particularly in long-duration regimens. Several studies have reported a correlation between ADRs and adherence to ARV therapy. Meanwhile, ARV is the main determinant of achieving an immunological and virologic response. Pharmacists play the role of counselors in improving therapeutic outcomes including ADR management. This study aimed to analyze ADRs induced by ARV based on pharmacy documentation and to describe the frequency of PLWH follow-up visits over a two-year period. The study was conducted at Sleman Regional Hospital, an HIV/AIDS referral hospital in Yogyakarta. A cross-sectional design was used with saturated sampling, including all ARV use for HIV/AIDS. Data were collected from the pharmacy unit and patients’ spontaneous reports. Prescribed ARV came from the electronic system, whereas ADR reports were from patients during voluntary consultation with the pharmacist or in PITC services. A total of 110 ARV were administered mostly to male patients aged 25-40 years. The most regimen was tenofovir+lamivudine+efavirenz (91%) with the highest frequency of follow-up visits ? 12 times (53%). The top three ADRs were dizziness (30%), nausea (11%), and headache (8%). Three of the four pediatric patients experienced ADRs, each with AZT-induced fatigue, bloating, and diarrhea in LPV/r monotherapy. Most of the patients did not maintain appointments for hospital visits. Further studies are recommended to analyze the causative factors of non-adherence, including the loss to follow-up group. Keywords: Adverse Drug Reaction, Antiretroviral, Hospital, Indonesia